(untitled) (International Journal of Food and Nutritional Sciences, 2024)
The men’s kabaddi team from Vinayaka Mission College of Physical Education in Salem, Tamil Nadu, was randomly chosen to comprise the twelve (12) participants of the research. Included were both sexes, with the age range being 21–28. Athletes participating at the college level were chosen at random. The chosen participants worked out with medicine balls every other week for six weeks. Among the fitness-related traits, anaerobic capacity and explosive power were the determining factors. We used a standardized exam to look at the qualities we had already chosen. Twelve men’s kabaddi players from collegiate teams make up the sample for this study. All participants were given a battery of skills assessments before and after the training. A single-group design with pre- and post-tests was used for participant selection. Using a single group’s pre- and post-test results, researchers recruited individuals.